Differential current-sensing for on-chip interconnects. - Maheshwari, A. (IEEE Transactions on VLSI systems)
This paper presents a differential current-sensing technique as an alternative to existing circuit techniques for on-chip interconnects. Using a novel receiver circuit, it is shown that, delay-optimal current-sensing is a faster (20% on an average) option as compared to the delay-optimal repeater insertion technique for single-cycle wires. Delay benefit for current-sensing increases with an increase in wire width. Unlike repeaters, current-sensing does not require placement of buffers along the wire, and hence, eliminates any placement constraints. Inductive effects are negligible in differential current-sensing. Current-sensing also provides a tighter bound on delay with respect to process variations. However, current-sensing has some drawbacks. It is power inefficient due to the presence of static-power dissipation. Current-sensing is essentially a low-swing signaling technique, and hence, it is sensitive to full swing aggressor noise.